Adam's life reflected in gayle forman's where she went novel (2011) :An individual psychological approach - Puspitasari, Amelia, Titis Setyabudi, S.S. M. Hum (2016)
The main issue of this research is life. If someone wants his life to be better he has to try and work hard. The purpose of this research is to analyze Where She Went novel based on the theory of individual psychology. The researcher used qualitative method. The researcher used two data sources: primer and secondary. The primer data was Where She Went novel written by Gayle Forman. The secondary data was supporting data taken from the theory of individual psychology books, and some articles from the internet related to the novel. For data collection method, the researcher used descriptive qualitative research. Based on this analysis, the researcher took some conclusions. This study shows that a problem faced by the main character was his life. It can be proved by his desire to fix his life to be better. It is prove by main character's hard work in making his desire to get better and happier life.